2016
DOI: 10.14710/jitaa.41.4.209-215
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calf Starter Ration for Pre-Weaning Ongole Grade (Po) Calves on Body Weight Gain

Abstract: The objective of study was to determine the effect of calf starter in the pre-weaning calves against the daily body weight gain. Twenty Ongole grade (PO) calves age of 1 month divided into 4 treatment groups of feed, 5 calves for each treatment. Treatment (P1) fed with extra soybean groats; (P2) soybean groats 50% + Gliricidia 50%; (P3) soybean groats 50%+ rice bran 50%; (P4) soybean groats 50%+ rejected bread 50%. Calf starter was given at age 1 month to 3 months. Observation was carried out on calves daily w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…in the range of 44 -80 kg. The similar final body weight of the preweaning calves obtained in the recent research was also reported by many researchers (Winarti and Widyastuti, 2016;Casper et al, 2017;de Assis Lage et al, 2019;Wickramasinghe et al, 2019). Better ADG of the preweaning calves in the recent research also reported by Hill et al (2016) who fed milk replacer combined with functional fatty acids, or Tao et al (2018) who fed milk replacer contained higher CP (23.94%).…”
Section: Body Weightsupporting
confidence: 86%
“…in the range of 44 -80 kg. The similar final body weight of the preweaning calves obtained in the recent research was also reported by many researchers (Winarti and Widyastuti, 2016;Casper et al, 2017;de Assis Lage et al, 2019;Wickramasinghe et al, 2019). Better ADG of the preweaning calves in the recent research also reported by Hill et al (2016) who fed milk replacer combined with functional fatty acids, or Tao et al (2018) who fed milk replacer contained higher CP (23.94%).…”
Section: Body Weightsupporting
confidence: 86%
“…Another study by Suyadi et al (2014) reported that Ongole Grade cattle or Benggala is a crossbreed result of uncontrolled mating of Sumba Ongole cattle and Java cattle. Moreover, as reported by previous studies, Ongole Grade cattle had 31.88±3.78 kg of average birth weight, 94.46±2.12 kg of average weaning weight, and 358±24.6 kg of average mature weight with 0.70 kg of average daily weight gain (Winarti and Widyastuti 2016;Maharani et al 2017;Maharani et al 2018).…”
Section: Introductionsupporting
confidence: 80%